Gliomas - Debinski, Waldemar (Exon Publications, 2021)
Gliomas are the primary brain tumors of the central nervous system. The prognosis, especially for high-grade gliomas, is dismal; the treatment of these tumors represents an unmet need in medicine. This book, contributed by an excellent team of clinicians and basic scientists, touches upon several critical aspects of glioma research and clinical therapies. There is a considerable emphasis on translational efforts. The 13 chapters of the book cover aspects of clinically-relevant models, glioma stem-like cells, IDH mutations, integrated approach for better patient outcome, abnormal cholesterol and other metabolic processes, bioinformatics for survival prediction, molecular signature for prognostication, neuro-functional monitoring during surgery, glioma-related epilepsy, and glioneuronal tumors along with various natural and synthetic drug candidates currently under evaluation. As such, the individual contributions provide a glimpse on the magnitude of challenges and potential solutions in a variety of research areas. This book will likely be interest to a wide audience seeking more information on challenges gliomas present to both scientists and clinicians.